2016
DOI: 10.2196/jmir.5585
|View full text |Cite
|
Sign up to set email alerts
|

Google Flu Trends Spatial Variability Validated Against Emergency Department Influenza-Related Visits

Abstract: BackgroundInfluenza is a deadly and costly public health problem. Variations in its seasonal patterns cause dangerous surges in emergency department (ED) patient volume. Google Flu Trends (GFT) can provide faster influenza surveillance information than traditional CDC methods, potentially leading to improved public health preparedness. GFT has been found to correlate well with reported influenza and to improve influenza prediction models. However, previous validation studies have focused on isolated clinical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…The online data search volumes showed a significant correlation with the observed weekly incidence. A temporal similarity has already been described in two previous studies (Pesala et al, 2017;Seifter et al, 2010) Cook, Conrad, Fowlkes, & Mohebbi, 2011;Dugas et al, 2012Dugas et al, , 2013Klembczyk et al, 2016;Ortiz et al, 2011), as already discussed in the Section 1. To avoid pitfalls that led to the failure of this application, we have used the results from Google searches to supplement the traditional method (instead of replacing it).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The online data search volumes showed a significant correlation with the observed weekly incidence. A temporal similarity has already been described in two previous studies (Pesala et al, 2017;Seifter et al, 2010) Cook, Conrad, Fowlkes, & Mohebbi, 2011;Dugas et al, 2012Dugas et al, , 2013Klembczyk et al, 2016;Ortiz et al, 2011), as already discussed in the Section 1. To avoid pitfalls that led to the failure of this application, we have used the results from Google searches to supplement the traditional method (instead of replacing it).…”
Section: Discussionsupporting
confidence: 64%
“…Google Trends, Twitter and other social media platform data offer an interesting tool to monitor public attention with regard to specific infectious diseases (Al‐Surimi, Khalifa, Bahkali, El‐Metwally, & Househ, ; Goff, Kullar, & Newland, ; Martin, Xu, & Yasui, ). Several studies have shown that this quantifiable attention is a good proxy for disease activity (Dugas et al, ; Klembczyk et al, ; Martin, Lee, & Yasui, ; Pollett et al, ; Strauss, Castro, Reintjes, & Torres, ; Thompson, Malik, Gumel, Strome, & Mahmud, ). Thus, these data can help to monitor and predict infectious diseases, especially in developing areas where traditional epidemiologic surveillance faces multiple challenges (Gluskin, Johansson, Santillana, & Brownstein, ; Strauss et al, ; Teng et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Google Flu Trends, which employed the service to provide information about flu activity in many countries, is perhaps the most well-known use of Google Trends data. [11][12][13] Other areas where Google Trends has been used are foot and ankle pain, 14 bariatric surgery, 15 and Lyme disease. 16 Tracking searches for disease terms can provide insight into possible reasons for searches of those terms.…”
Section: Introductionmentioning
confidence: 99%
“…Studying Internet search patterns has facilitated opportunities for evaluating public interest encompassing a variety of topics. Extrapolating data from a portion of 3 billion searches daily, Google Trends represents a powerful tool for gauging public interest and has demonstrated its unique value in numerous analyses . Upon comparison of search volume trends with other common cancers, OPC demonstrated a notable increase over the 11‐year period available, suggesting growing public interest (Fig.…”
Section: Discussionmentioning
confidence: 99%